2010
DOI: 10.1258/ult.2010.009001
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic methods for quantification of left ventricular ejection fraction: are they interchangeable?

Abstract: This study examined the relationships between left ventricular ejection fraction data derived from four commonly used cardiac ultrasound measurement methods (visual estimation, wall motion scoring, biplane Simpson's method and three-dimensional [3D] echocardiography) to assess whether they can be used interchangeably in the assessment of left ventricular systolic function. Two-dimensional (2D) and 3D data obtained from ultrasound studies for 190 patients (109 men, mean age 56 + 20 standard deviation [SD] years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…The data on subjective visual assessment of LV function were the most complete and were therefore used in the multivariable analysis when considering LV systolic function. Although visual estimation of LV function can be performed on poor-quality images, it requires high levels of sonographer and cardiologist experience to be accurate and reproducible (38). It was not possible to determine the level of sonographer experience in this study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The data on subjective visual assessment of LV function were the most complete and were therefore used in the multivariable analysis when considering LV systolic function. Although visual estimation of LV function can be performed on poor-quality images, it requires high levels of sonographer and cardiologist experience to be accurate and reproducible (38). It was not possible to determine the level of sonographer experience in this study.…”
Section: Discussionmentioning
confidence: 94%
“…All echocardiographic methods of estimation of LV function are subject to error. Although the wall motion scoring method and biplane Simpson's method have subjective components (38), a 2003 review found that the degree of agreement between subjective visual assessment and reference methods was similar to that obtained with Simpson's rule for the calculation of LVEF (39). Another limitation was that cause of death in Australia and New Zealand Dialysis and Transplant Registry is reported by the treating center and is not based on autopsy reports, so there are likely to be errors in the classification of cause of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the subjects were in the left lateral decubitus position, two-dimensional, pulsed-wave Doppler transmitral recordings and tissue Doppler imaging (TDI) recordings of the mitral annulus diastolic velocities were performed with conventional views (parasternal long and short axes, apical 4-chamber) by a cardiologist with a 3.5-MHz sector transducer (Esaote MyLab 50, Genoa, Italy) and with simultaneously ECG recordings according to the recommendations of the American Society of Echocardiography (ASE) proposals (16) . Ejection fraction and left ventricle mass index (LVMI) were determined as described previously (17,18) . We performed pulsed-wave Doppler to measure mitral infl ow velocity in apical 4-chamber view during diastole.…”
Section: Echocardiographymentioning
confidence: 99%
“…The authors did not state how left ventricular ejection fraction was assessed nor if the same technique was used by all operators. Four standard methods (Simpson’s biplane, Teicholz, wall‐motion scoring and ‘eyeballing’) are poorly interchangeable [7]. The first two do not correlate well with left ventricular ejection fraction in left ventricular hypertrophy [8] and are affected differently by permanent cardiac pacing [9].…”
mentioning
confidence: 99%